STREET LIGHTS INTELLIGENT SYSTEM, BASED ON THE INTERNET OF THINGS CONCEPT - CYGAN, Sebastian; BOROWIK, Barbara; BOROWIK, Bohdan (Applied Computer Science, 2018)
The paper presents a project of a street lights intelligent system, which allows for public savings, as a result of more efficient roads and pavements lights management. The system would operate based on the current location of vehicles and pedestrians. Because of this no additional costs or devices are required in smartphones or modern vehicles to indicate its location, as smartphones, smartwatches and most of modern cars are equipped with the GPS modules. But each smart street lamp needs to be equipped with a little module that communicates with the central system and which controls the work of lighting.